The frequency usage of i-learn portal among lecturers in Faculty of Business Management in Universiti Teknologi MARA, Kedah / Nurul Azmira Yaacob - Yaacob, Nurul Azmira (Faculty of Information Management, 2012)
This study is about the frequency usage of i-learn portal among the lecturers in Faculty of Business Management in Universiti Teknologi MARA, Kedah. is a learning management system for e-learning in UiTM. Relevant to today's technological advancement, system acts as a platform that supports the teaching and learning process in UiTM. The objectives of this study are to identify the frequency usage of i-learn portal among lecturers, to study the roles of lecturers as a depositor in i-learn portal and to identify the reasons of the lecturer’s act as a user of i-learn portal. The questionnaires will be distributed in order to collect the data and the data will be analysis by use the software known as Statistical Package for Social Science (SPSS) version 17.0. The Stratified Random Sampling will be used as sampling design because it only focuses on the lecturer in faculty of Business Management. As conclusion, the level usage of i-learn and the roles of lecturers toward i-learn portal is the factor that influence the learning process in Universiti Teknologi MARA